Food security as a response to AIDS: IFPRI 2001-2002 Annual Report Essay - Gillespie, Stuart; Haddad, Lawrence J. (International Food Policy Research Institute, 2002)
The HIV/AIDS pandemic in Sub-Saharan Africa has become increasingly intertwined with issues of food and nutrition. On the one hand, malnutrition and food insecurity may force households to adopt livelihoods that increas the risk of HIV transmission, such as migration to find work. On the other, HIV/AIDS may precipitate or exacerbate malnutrition and food insecurity.